Exploring the awareness on green human resource development practices among hotel industry employees in Lagos State, Nigeria: a preliminary study - Osolase, Ehikioya Hilary; Mohd Rasdi, Roziah; Dato’ Mansor, Zuraina (Human Resource Management Academic Research Society, 2022)
The purpose of this study is to explore awareness on green human resource development practices among employees of the hotel industry in Lagos State, Nigeria. Over the past decade, the impact from climate change and global warming has led to environmental degradation. This is because of the harmful activities conducted on the natural environment by employees and various organizations, of which the hotel industry is part of. The overconsumption of energy and water, and the use of products and materials which are considered harmful to the environment. Lack of effective waste disposal mechanisms, and the inability to recycle, are all harmful to the environment. Globally, the hotel industry is a major employer of labour, therefore, to help mitigate these harmful practices, there is the need for the hotel industry in Nigeria to adopt green human resource development (Green HRD) practices. This is to help transform the natural environment back to its original state. The method of data collection for the study is structured interview, which is a qualitative study. Two employees working in the same hotel participated in the study. The outcome from the preliminary investigation revealed that, although employees had awareness on what green practices means, but lacked knowledge on green training and development, which is a Green HRD practice. Participants also lack knowledge on the meaning of Green HRD. Additionally, employees’ investigated lacked green skills, competencies, and abilities, which are outcomes of green training and development and green human capital. Employees’ awareness on green practices were through printed handbills distributed by the manager of the hotel to each employee. To strengthen employees green skills, knowledge, behaviours, and abilities in the investigated hotel, and for the successful implementation of Green HRD practices, there is the need to invest on green training and development. Green training and development will help to strengthen the green human capital of the explored hotel, so as to be able to achieve environmental performance. Due to the number of few participants which took part in the study, subsequent researches can focus on a larger number of participants among employees in Nigeria's hotel industry, as this may lead to a broader outcome and perspective.